Control Development of Series Compensator (TCSC) and Stability Enhancement in the Interconnected Power Systems - عبد الحميد محمد; بدر زيد; سليمان نور الدين (Latakia University Journal -Engineering Sciences Series, 2022)
This paper presents a new technique for controlling the series compensator in electric power networks. This method is based on the development of a hybrid controller consists of proportional integral and fuzzy logic. The results demonstrate a significant improvement in compensator behavior in terms of tracking a specific reference of added impedance in series with the power transmission line with the presence of proposed control. The performance of the compensator was also tested on an interconnected network between three electrical regions to prove the compensator’s effectiveness to achieve the high stability .The results showed that the failure leads the system goes of stability without a compensator, while the presence of the compensator allows maintaining stability when the faults occur. The simulation results in MATLAB software showed good performance of the control system in transient and steady states and the importance of using this type of compensator.